ISOTOPIC BIOGEOCHEMISTRY OF MARINE ORGANIC CARBON - Freeman K.H. (My University, 2001)
The ocean accounts for over 90% of the active pools of carbon on the Earth’s surface, with over 95% of marine carbon in the form of dissolved inorganic carbon (DIC) (Hedges and Keil 1995). Organic carbon dissolved in the ocean, suspended as particles or cells, and accumulating in sediments together constitute the other significant fractions of marine carbon, with organic carbon in the water column similar in quantity to the current atmospheric inventory of carbon dioxide. Isotopic partitioning among various inorganic and organic carbon phases reflects biological, physical and chemical processes, and the resulting fractionations are important tools...